The immaterial labor in Jum Nakao’s work - Giuriatti, Larissa P. [UNESP]; Pinheiro, Olympio José [UNESP] (Instituto Politecnico de Castelo Branco, 2023)
The article brings the question of the value of the immaterial labor of fashion design through the performance The Sewing of the Invisible, by Jum Nakao (2004). In a relationship between the production of fashion (immaterial) a symbolic, intangible product that meets a desire and the production of clothing (material) a concrete and tangible product is configured the product of fashion design. However, what would be the value of intellectual, immaterial production in such an ephemeral system? Would this value be associated only with the sales figures of the concrete product? Through a descriptive and qualitative research about the immaterial labor present in Nakao’s work, we sought to solve these questions and other reflections.
O TRABALHO IMATERIAL NA OBRA DE JUM NAKAO
Keywords: Fashion Design; Immaterial Labor; The Sewing of the Invisible